2007
DOI: 10.1007/s11199-007-9252-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Virtual Negotiation: Theory and Research

Abstract: Social roles create conflicting behavioral expectations for female negotiators; however, virtual negotiations reduce social pressures. This paper reviews theoretical explanations on why men and women might differ in negotiations that occur through email, telephone, or video. Forty-three negotiation studies comparing face-to-face and virtual negotiations were examined for gender differences. All studies were reported in English but not limited to US participants. While many reports omitted gender information, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 67 publications
3
43
1
1
Order By: Relevance
“…In contrast, Maurin et al [24] found that male paramedics have more favourable attitudes to collaborate with a remote physician than females. Stuhlmacher et al [25] found that women are significantly more aggressive when using computer-mediated communication technologies in comparison to face-to-face communication. This is in line with research by Wachter [26] who found that women feel more able to dominate the partner in a videoconferencing condition.…”
Section: Summary Of Cross-media Studiesmentioning
confidence: 99%
“…In contrast, Maurin et al [24] found that male paramedics have more favourable attitudes to collaborate with a remote physician than females. Stuhlmacher et al [25] found that women are significantly more aggressive when using computer-mediated communication technologies in comparison to face-to-face communication. This is in line with research by Wachter [26] who found that women feel more able to dominate the partner in a videoconferencing condition.…”
Section: Summary Of Cross-media Studiesmentioning
confidence: 99%
“…This includes the masculine job roles of leaders and managers (e.g., Eagly and Karau 2002;Eagly et al 1992), physicians (Burgoon et al 1991), scientists and engineers (Dodson and Borders 2006;Jagacinski 1987), accountants (Johnson and Scandura 1994), negotiators (e.g., Stuhlmacher et al 2007) and police officers (Martell 1991(Martell , 1996, as well as in feminine job roles such as nurses (Kirchmeyer 1997) and elementary school counselors (Dodson and Borders 2006). Laboratory studies suggest that in masculine job roles men are preferred over women, while in feminine job roles women are preferred over men (Davidson and Burke 2000).…”
Section: Role Congruitymentioning
confidence: 99%
“…The congruence of the mediator's gender role and job role is expected to influence the evaluation of the disputant. While role congruity has been suggested as a factor in gender differences in negotiation (Stuhlmacher et al 2007), the questions of gender issues in the related field of mediation remains underexplored (Stuhlmacher and Morrissett 2008). This is surprising given that mediation is a popular way to address conflict in families, work organizations, communities, and international disagreements (Kressel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…mation gathering on decision-making; Stuhlmacher et al (2007) analysed the different ways of negotiation determined by gender in virtual negotiations; Gibler and Nelson (2003) analysed the behaviour of real estate consumers. Some researchers tend to re-examine previous works related to the issues they have selected and to repeat previous experiments taking up a perspective of a new paradigm.…”
Section: The Conceptual Model Of Construction and Real Estate Negotiamentioning
confidence: 99%